Tumor talk: A descriptive study of communication about tumor board meetings - Jillian A. Tullis (Qualitative Research in Medicine & Healthcare)
Tumor board meetings are behind-the-scenes settings where communication about health and strategizing about healthcare delivery take place. Despite their wide use in hospitals and cancer centers, there is a dearth of information about the communication practices in this context. Drawing upon six weeks of observations, this study investigated communication during tumor board meetings at a tertiary cancer center in the Southeastern United States. Findings revealed differences in communication among cancer specialties, with one tumor board consistently talking about the medical and non-medical elements of patient cases, while other specialties focused primarily on plans for treatment with little discussion about quality of life, economic, or caregiver support issues. The manuscript includes suggestions for modifying tumor conferences and opportunities for future research.